Is Transreligious Theology Unavoidable in Interreligious Theology and Dialogue? - Gustafson, Hans (Open theology, 2016)
This article investigates whether transreligious theology is unavoidable in the doing of interreligious theology and dialogue. In so doing, it opens with three examples that point the way to transreligious theology (Wilfred Cantwell Smith, Keith Ward, and Francis Clooney). Various prefixes are then defined and distinguished from one another as they are often applied to the term "religious" (uni-, intra-, multi-, cross-, inter-, and trans-). These prefixes are then applied to the terms "dialogue" (transreligious dialogue) and "theology" (transreligious theology). In particular, transreligious theology is set apart by a) taking seriously the fluid and porous borders of religion and religious identities, and b) its requirement of generating something novel beyond the already established religious traditions. The question is then asked whether transreligious theology is unavoidable in the context of interreligious theology dialogue, given the vast complexity of religious identities. The article culminates by addressing two lingering challenges to transreligious theology, the perceived specter of creeping syncretism and the possibility of "frustration overload" due to the overwhelming complexity of religions and religious identities.